2020
DOI: 10.1038/s41598-020-76564-7
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A augments angiogenic pathways in skeletal muscle by bolstering NAD+ and SIRT1

Abstract: Urolithin A (UA) is a natural compound that is known to improve muscle function. In this work we sought to evaluate the effect of UA on muscle angiogenesis and identify the underlying molecular mechanisms. C57BL/6 mice were administered with UA (10 mg/body weight) for 12–16 weeks. ATP levels and NAD+ levels were measured using in vivo 31P NMR and HPLC, respectively. UA significantly increased ATP and NAD+ levels in mice skeletal muscle. Unbiased transcriptomics analysis followed by Ingenuity Pathway Analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 73 publications
0
48
0
Order By: Relevance
“…Next to increased PGC1α gene expression, Andreux et al also found that 1000 mg/day UA led to significant increases of ESRRα and significantly higher mitochondrial mass in subjects’ skeletal muscle [ 37 ]. In skeletal muscle myoblasts of C57BL/6 mice treated with 10 mg/kg bodyweight UA, Ghosh et al found increased PGC1α and SIRT1 expression, as well as increased ATP levels [ 39 ]. Since it is not unambiguously clear in which way PGC1a was or was not affected due to its short half-life, alternatives should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to increased PGC1α gene expression, Andreux et al also found that 1000 mg/day UA led to significant increases of ESRRα and significantly higher mitochondrial mass in subjects’ skeletal muscle [ 37 ]. In skeletal muscle myoblasts of C57BL/6 mice treated with 10 mg/kg bodyweight UA, Ghosh et al found increased PGC1α and SIRT1 expression, as well as increased ATP levels [ 39 ]. Since it is not unambiguously clear in which way PGC1a was or was not affected due to its short half-life, alternatives should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Low doses of UA have also been reported to provide neuroprotection against H 2 O 2 induced oxidative stress in N2a [ 33 ] and SH-SY5Y [ 34 , 35 ] cells. Furthermore, multiple studies also reported increased mitochondrial function and enhanced mitochondrial biogenesis facilitated by UA [ 27 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…PKCζ can regulate the activity of Sirt1, which is a deacetylating enzyme of NAD + depletion that has significant antioxidant activity by deacetylating various substrates involved in gene silencing, cell cycle, and aging processes (40). The activation of Sirt1 can significantly improve endothelial function in aged mice (41), decrease the expression of Keap1 that can lead to the dissociation and nuclear translocation of Nrf2, activate Keap1/Nrf2 antioxidant pathway, and thus activate the transcriptions of a variety of antioxidant genes, including NQO1 and GST (42,43). Therefore, inhibition of PKCζ can decrease the production of ROS and alleviate oxidative stress through regulating Sirt1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When administered intragastrically to middle-aged mice for 16 weeks, UA increased markers of angiogenesis in the skeletal muscle [37]. Although no functional data were provided, this is a relevant observation, as impaired neovascularization plays an important role in muscle aging diseases [38].…”
Section: Open Accessmentioning
confidence: 99%